Wildlife Harvesting and Sustainable Regional Native Economy in the Hudson and James Bay Lowland, Ontario - Berkes, F.; George, P.J.; Preston, R.J.; Hughes, A.; Turner, J.; Cummins, B.D. (ARCTIC, 1994)
To assist the Omushkego Cree in planning a community and regional economic development strategy that takes into account the traditional economy, we developed appropriate methodologies to investigate the quantitative importance and economic value of hunting and fishing for the Mushkegowuk region, Hudson and James Bay Lowland. Harvests of wildlife by the 6500 aboriginal residents of eight communities - Moose Factory, Moosonee, New Post, Fort Albany, Kashechewan, Attawapiskat, Peawanuck and Fort Severn - were estimated by means of a questionnaire study. A total of 925 persons were interviewed for 56% coverage in a stratified sampling design. Four species (moose, Canada goose, caribou, lesser snow goose) accounted for about two-thirds of the 1990 bush food harvest of 687 000 kg, the equivalent of 402 g meat or 97 g protein per adult per day. The replacement value of the bush food harvested in the region was about $7.8 million in 1990. Including other products of the land (fur, fuelwood, berries), the total value of the traditional economy, $9.4 million for the region or $8400 per household per year, was about one-third as large as the total cash economy. The results show that the traditional economy is a cornerstone of the regional mixed economy, and that such a mixed economy may persist as a culturally and environmentally sustainable base for the region.Key words: Hudson Bay and James Bay Lowland, Canadian subarctic, Cree, sustainable development, subsistence, wildlife, fisheries Dans le but d'aider les Cris Omushkego à planifier une stratégie de développement économique communautaire et régional qui tienne compte de l'économie traditionnelle, on a mis au point des méthodologies appropriées permettant d'enquêter sur l'importance quantitative et sur la valeur économique de la chasse et de la pêche pour la région de Mushkegowuk, dans les basses-terres de la baie d'Hudson et de la baie James. Une étude faite à l'aide d'un sondage a permis d'évaluer le nombre de prises d'animaux par les 6500 autochtones habitant les ...